MARKETING STRATEGY OF RUMAH DOMES NEW NGLEPEN PRAMBANAN TOURISM VILLAGE, SLEMAN REGENCY, SPECIAL REGION OF YOGYAKARTA - Chamidatuz, Aulia; Mahendra, Gerry Katon (Kemudi, 2024)
Nglepen Village, located in Sengir Hamlet, Sumberharjo, Sleman Regency, has a one-of-a-kind tourist destination in Indonesia, namely Rumah Domes New Nglepen Tourism Village. This study aims to determine the marketing strategy carried out by the manager of Rumah Domes New Nglepen Tourism Village. It also aims to know the supporting and inhibiting factors of the marketing strategy carried out by the manager of Rumah Domes New Nglepen Tourism Village. The research method that the author used was qualitative descriptive with key informants and supporting informants. Data were obtained through informants, activities, places or locations, and documents or archives. Data collections techniques in this study were observation, documentation, and interviews. The main finding of the study is that Rumah Domes New Nglepen Tourism Village has successfully implemented the exposure and interest of dome houses. The suggestion to increase exposure and interest in dome houses is that managers are expected to not only promote through events and collaborations, considering that, in this day and age, everything utilizes social media. The manager of Rumah Domes New Nglepen Tourism Village can collaborate with Pokdarwis (tourism awareness group) to create social media accounts on behalf of Rumah Domes New Nglepen Tourism Village on Instagram, Tiktok, Twitter, Facebook, and YouTube and to create routine content related to Rumah Domes New Nglepen which will be uploaded on the social media accounts of Rumah Domes New Nglepen Tourism Village.